GENDER FEATURES OF UNITS EXPRESSING AESTHETIC VALUE IN A LITERARY TEXT - Marufova Zulfiya Nabiyevna (Journals Park Publishing, 2023)
The article examines the interpretation of the concept of “beauty” in works of art, and research conducted by linguists on this topic. The problem of gender identity in the expression of beauty is also analyzed using the example of Uzbek fiction.
Keywords: beauty, gender, pattern, national-aesthetic assessment, verbalization, standard, conceptualization, ideal.